Susceptibility profiles and resistance genomics of Pseudomonas aeruginosa isolates from European ICUs participating in the ASPIRE-ICU trial. (22nd April 2022) - Torrens, Gabriel; van der Schalk, Thomas Ewout; Cortes-Lara, Sara; Timbermont, Leen; del Barrio-Tofiño, Ester; Xavier, Basil Britto; Zamorano, Laura; Lammens, Christine; Ali, Omar; Ruzin, Alexey; Goossens, Herman; Kumar-Singh, Samir; et al.
Abstract: Objectives: To determine the susceptibility profiles and the resistome of Pseudomonas aeruginosa isolates from European ICUs during a prospective cohort study (ASPIRE-ICU). Methods: 723 isolates from respiratory samples or perianal swabs of 402 patients from 29 sites in 11 countries were studied. MICs of 12 antibiotics were determined by broth microdilution. Horizontally acquired β-lactamases were analysed through phenotypic and genetic assays. The first respiratory isolates from 105 patients providing such samples were analysed through WGS, including the analysis of the resistome and a previously defined genotypic resistance score. Spontaneous mutant frequencies and the genetic basis of hypermutation were assessed. Results: All agents except colistin showed resistance rates above 20%, including ceftolozane/tazobactam and ceftazidime/avibactam. 24.9% of the isolates were XDR, with a wide intercountry variation (0%–62.5%). 13.2% of the isolates were classified as DTR (difficult-to-treat resistance). 21.4% of the isolates produced ESBLs (mostly PER-1) or carbapenemases (mostly NDM-1, VIM-1/2 and GES-5). WGS showed that these determinants were linked to high-risk clones (particularly ST235 and ST654). WGS revealed a wide repertoire of mutation-driven resistance mechanisms, with multiple lineage-specific mutations. The most frequently mutated genes were gyrA, parC, oprD, mexZ, nalD and parS, but only two of the isolates were hypermutable. Finally, a good accuracy of the genotypic score to predict susceptibility (91%–100%) and resistance (94%–100%) was documented. Conclusions: An overall high prevalence of resistance is documented European ICUs, but with a wide intercountry variability determined by the dissemination of XDR high-risk clones, arguing for the need to reinforce infection control measures.